ChemInform Abstract: Laminar MoS2 Membranes for Molecule Separation. Issue 4 (28th January 2014) - Sun, Luwei; Huang, Hubiao; Peng, Xinsheng
Abstract New laminar separation membranes are prepared from atom‐thick chemically exfoliated micrometer sized MoS2 sheets by the vacuum filtration technique.